Dietary Fiber Pectin Directly Blocks Toll-Like Receptor 2–1 and Prevents Doxorubicin-Induced Ileitis - Sahasrabudhe, Neha M.; Beukema, Martin; Tian, Lingmin; Troost, Berit; Scholte, Jan; Bruininx, Erik; Bruggeman, Geert; van den Berg, Marco; Scheurink, Anton; Schols, Henk A.; Faas, Marijke M.; de Vos, Paul (Frontiers in Immunology, 2018)
Dietary carbohydrate fibers are known to prevent immunological diseases common in Western countries such as allergy and asthma but the underlying mechanisms are largely unknown. Until now beneficial effects of dietary fibers are mainly attributed to fermentation products of the fibers such as anti-inflammatory short chain fatty acids. Here, we found and present a new mechanism by which dietary fibers can be anti-inflammatory: a commonly consumed fiber, pectin, blocks innate immune receptors. We show that pectin binds and inhibits, Toll-like receptor 2 (TLR2) and specifically inhibits the proinflammatory TLR2-TLR1 pathway while the tolerogenic TLR2-TLR6 pathway remains unaltered. This effect is most pronounced with pectins having a low degree of methyl esterification (DM). Low DM pectin interact with TLR2 through electrostatic forces between non-esterified galacturonic acids on the pectin and positive charges on the TLR2 ectodomain, as confirmed by testing pectin-binding on mutated TLR2. The anti-inflammatory effect of low DM pectins was first studied in human dendritic cells and mouse macrophages in vitro and was subsequently tested in vivo in TLR2 dependent ileitis in a mouse model. In these mice, ileitis was prevented by pectin administration. Protective effects were shown to be TLR2-TLR1-dependent and independent of the short chain fatty acids (SCFA) produced by the gut microbiota. These data suggest that low DM pectins as a source of dietary fiber can reduce inflammation through direct interaction with TLR2-TLR1 receptors.